Numerical modelling of microwave heating treatment for tight gas sand reservoirs - Wang, Hongcai; Rezaee, M. Reza; Saeedi, Ali; Josh, M. (Elsevier, 2017)
Formation Heat Treatment (FHT) has been proved effective in removing water phase and creating micro-fractures in the near wellbore area previously. In order to improve the cost and time efficiency of FHT, microwave heater is considered as an alternative in this paper, and its feasibility in FHT is discussed in this paper. Numerical simulation is carried out to investigate the effects of microwave heating on reservoir quality and gas production. It is found that the water phase can be effectively removed by microwave heating, as a result, the relative permeability to gas increased significantly after heating. In terms of gas production rate, the cumulative gas in 90 days in heated well is 4×105 m3 more than the non-heated well. As the most important parameter, the temperature distributions in the reservoir are computed with two methods and their value against the heating depth agree with each other reasonably. On the other hand, the surface temperature variations of tlhree tight sandstone plugs are heated with microwave in the lab and their surface temperatures are carefully recorded against time. Then the laboratory data are compared with simulation results, and they correlate well with each other. The simulation work conducted in this paper shows the promising improvement of gas relative permeability and production by microwave heating.